Improved angiographic findings in a high risk acute coronary syndrome patient after modest weight reduction, regular exercise and medication: A case report and literature review - Veerakul, Gumpanart; Kitkungvan, Thadchai; Bhatia, Nirmal (The Bangkok Medical Journal, 2012)
A 55<span style="mso-bidi-font-size: 11.0pt; line-height: 107%; font-family: 'Angsana New','serif'; mso-ascii-font-family: Calibri; mso-ascii-theme-font: minor-latin; mso-hansi-font-family: Calibri; mso-hansi-theme-font: minor-latin;">-year<span style="mso-bidi-font-size: 11.0pt; line-height: 107%; font-family: 'Angsana New','serif'; mso-ascii-font-family: Calibri; mso-ascii-theme-font: minor-latin; mso-hansi-font-family: Calibri; mso-hansi-theme-font: minor-latin;">-old, morbidly obese man body weight <span style="mso-bidi-font-size: 11.0pt; line-height: 107%; font-family: 'Angsana New','serif'; mso-ascii-font-family: Calibri; mso-ascii-theme-font: minor-latin; mso-hansi-font-family: Calibri; mso-hansi-theme-font: minor-latin;">(BW<span style="mso-bidi-font-size: 11.0pt; line-height: 107%; font-family: 'Angsana New','serif'; mso-ascii-font-family: Calibri; mso-ascii-theme-font: minor-latin; mso-hansi-font-family: Calibri; mso-hansi-theme-font: minor-latin;">) of 104 kg, body mass index <span style="mso-bidi-font-size: 11.0pt; line-height: 107%; font-family: 'Angsana New','serif'; mso-ascii-font-family: Calibri; mso-ascii-theme-font: minor-latin; mso-hansi-font-family: Calibri; mso-hansi-theme-font: minor-latin;">(BMI<span style="mso-bidi-font-size: 11.0pt; line-height: 107%; font-family: 'Angsana New','serif'; mso-ascii-font-family: Calibri; mso-ascii-theme-font: minor-latin; mso-hansi-font-family: Calibri; mso-hansi-theme-font: minor-latin;">) of 30<span style="mso-bidi-font-size: 11.0pt; line-height: 107%; font-family: 'Angsana New','serif'; mso-ascii-font-family: Calibri; mso-ascii-theme-font: minor-latin; mso-hansi-font-family: Calibri; mso-hansi-theme-font: minor-latin;">.5 kg<span style="mso-bidi-font-size: 11.0pt; line-height: 107%; font-family: 'Angsana New','serif'; mso-ascii-font-family: Calibri; mso-ascii-theme-font: minor-latin; mso-hansi-font-family: Calibri; mso-hansi-theme-font: minor-latin;">/m2 with known history of type 2 diabetes mellitus, hypertension, dyslipidemia and primary hypothyroidism, presented with acute chest pain and heart failure in 2007<span style="mso-bidi-font-size: 11.0pt; line-height: 107%; font-family: 'Angsana New','serif'; mso-ascii-font-family: Calibri; mso-ascii-theme-font: minor-latin; mso-hansi-font-family: Calibri; mso-hansi-theme-font: minor-latin;">. Frank pulmonary edema and cardiomegaly were documented from admission chest film <span style="mso-bidi-font-size: 11.0pt; line-height: 107%; font-family: 'Angsana New','serif'; mso-ascii-font-family: Calibri; mso-ascii-theme-font: minor-latin; mso-hansi-font-family: Calibri; mso-hansi-theme-font: minor-latin;">(Figure 1<span style="mso-bidi-font-size: 11.0pt; line-height: 107%; font-family: 'Angsana New','serif'; mso-ascii-font-family: Calibri; mso-ascii-theme-font: minor-latin; mso-hansi-font-family: Calibri; mso-hansi-theme-font: minor-latin;">). The electrocardiogram <span style="mso-bidi-font-size: 11.0pt; line-height: 107%; font-family: 'Angsana New','serif'; mso-ascii-font-family: Calibri; mso-ascii-theme-font: minor-latin; mso-hansi-font-family: Calibri; mso-hansi-theme-font: minor-latin;">(ECG<span style="mso-bidi-font-size: 11.0pt; line-height: 107%; font-family: 'Angsana New','serif'; mso-ascii-font-family: Calibri; mso-ascii-theme-font: minor-latin; mso-hansi-font-family: Calibri; mso-hansi-theme-font: minor-latin;">) (Figure 2<span style="mso-bidi-font-size: 11.0pt; line-height: 107%; font-family: 'Angsana New','serif'; mso-ascii-font-family: Calibri; mso-ascii-theme-font: minor-latin; mso-hansi-font-family: Calibri; mso-hansi-theme-font: minor-latin;">) showed sinus tachycardia, left atrial enlargement, tall R in V2 with ST depression in V2<span style="mso-bidi-font-size: 11.0pt; line-height: 107%; font-family: 'Angsana New','serif'; mso-ascii-font-family: Calibri; mso-ascii-theme-font: minor-latin; mso-hansi-font-family: Calibri; mso-hansi-theme-font: minor-latin;">-4, Q wave and mild ST segment elevation in inferior leads<span style="mso-bidi-font-size: 11.0pt; line-height: 107%; font-family: 'Angsana New','serif'; mso-ascii-font-family: Calibri; mso-ascii-theme-font: minor-latin; mso-hansi-font-family: Calibri; mso-hansi-theme-font: minor-latin;">.